Interaction of Sambiloto (Andrographis paniculata) Bioactive Compound with Milk Protein (Whey and Casein) Through Molecular Docking and Molecular Dynamics Simulation as a Basis for Encapsulation - Premy Puspitawati Rahayu; Manik Eirry Sawitri; Dwi Setiawan; Citra Nurma Yunita (Postgraduate, University of Mataram, 2024)
This research aims for developing immune-boosting products necessary. The active ingredient in Andrographis paniculate (AP) acts as an immunostimulant which can improve the work of the immune system. The first stage of research was a collection of bioactive compounds from KnapSack database of Kanaya, Dr. Duke's Phytochemical and Ethnobotanical were compiled and selected based on the online pass results of each bioactive compound as an immunomodulator and 10 active compounds were obtained which will be continued. The second stage of research was a docking molecular between whey proteins (β-lactoglobulin and α-lactalbumin) with active compounds from AP and casein (α-Casein, β-Casein, and κ-Casein). The highest binding affinity was obtained for α-Casein with Neoandrographolide at -9.2 Kcal/mol. The results of the complex α-Casein with Neoandrographolide (CC) and α-Casein with Neoandrographolide ultraheat (CCT) support the research, namely to function α-Casein as an encapsulant well as a transporter or drug delivery of Neoandrographolide without changing the conformation of casein and disturbing its function. However, the conformation of casein will change drastically during ultraheat treatment to maintain the conformation and binding with the Neoandrographolide ligand. In addition, it supports the simulation results of single α-Casein at ultraheat temperatures which show conformational stability that is not much different from single α-casein and complexes at physiological temperatures